Trypanosoma avium of raptors (Falconiformes): phylogeny and identification of vectors - Votýpka, J; Oborník, M; Volf, P; Svobodová, M; Lukes, J (Parasitology, 2002)
Avian trypanosomes are widespread parasites of birds, the transmission of which remains mostly unclear, with various blood-sucking insects mentioned as possible vectors. A search for vectors of trypanosomes of sparrowhawk (Accipiter nisus), buzzard (Buteo buteo), lesser-spotted eagle (Aquila pomarina) and kestrel (Falco tinnunculus) was performed in Czech and Slovak Republics. Black flies (Eusimulium spp.), hippoboscid flies (Ornithomyia avicularia), mosquitoes (Culex pipiens pipiens) and biting midges (Culicoides spp.), trapped while attempting to feed on raptor nestlings, were found to contain trypanosomatids in their intestine. Trypanosomes from the raptors and blood-sucking insects were isolated, and their 18S rRNA sequences were used for species identification and for the inference of intra- and interspecific relationships. Together with the trypanosome isolated from a black fly, the bird trypanosomes formed a well-supported Trypanosoma avium clade. The isolates derived from hippoboscid flies and mosquitoes are most likely also avian trypanosomes infecting birds other than the studied raptors. Analysis of the kinetoplast, that has features characteristic for the avian trypanosomes (minicircle size; dimensions of the kinetoplast disc), provided further evidence for the identification of vectors. It is suggested that all trypanosomes isolated from raptors included in this study belong to the T. avium complex and are transmitted by the ornithophilic simuliids such as Eusimulium securiforme.
Keywords: Animals; Base Sequence; RNA, Ribosomal, 18S; kinetoplastová DNA; Insect Vectors; druhová specificita; dravci; divoká zvířata; Trypanosoma; Molecular Sequence Data; nemoci ptáků; Species Specificity; Phylogeny; Bird Diseases; hmyz - vektory; molekulární sekvence - údaje; DNA, Kinetoplast; hmyz; Animals, Wild; sekvenční homologie nukleových kyselin; RNA ribozomální 18S; Raptors; sekvence nukleotidů; Sequence Homology, Nucleic Acid; zvířata; fylogeneze; Insecta